2021
DOI: 10.1007/s10862-021-09919-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact Battery: Development and Validation

Abstract: In addition to impacting the physical health of millions of Americans, the novel-coronavirus (COVID-19) pandemic is a significant psychological stressor due to both the threat of the illness itself and the mitigation strategies used to contain the spread. To facilitate understanding of the impact of COVID-19, validated measures are needed. Using a stepwise procedure in line with best-practice measurement procedures, the current report summarizes the procedures employed to create the COVID-19 Impact Battery (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Despite the strengths of the current study, including its longitudinal design and use of an empirically validated COVID-19related disability scale (i.e., the CIB disability scale; Schmidt et al, 2020), the present findings must be considered in the context of several limitations. Although the use of online crowdsourcing mechanisms, including Amazon's MTurk platform, is well-accepted, and attention check items were utilized to prevent the inclusion of automated responses, the findings from this sample should be interpreted with caution, as they may not be representative of the entire U.S. population.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the strengths of the current study, including its longitudinal design and use of an empirically validated COVID-19related disability scale (i.e., the CIB disability scale; Schmidt et al, 2020), the present findings must be considered in the context of several limitations. Although the use of online crowdsourcing mechanisms, including Amazon's MTurk platform, is well-accepted, and attention check items were utilized to prevent the inclusion of automated responses, the findings from this sample should be interpreted with caution, as they may not be representative of the entire U.S. population.…”
Section: Discussionmentioning
confidence: 95%
“…Items were used to specifically assess the impact of COVID-19 on household activities, day-to-day work, community activities, emotional health, concentration, getting along with new people, and maintaining friendships. The initial development and validation of the CIB disability scale evidenced strong reliability and validity, with Cronbach's alpha values for internal consistency ranging from .82 to .87; longitudinal measurement invariance showed a good fit; and the scale score related as expected to factors, such as negative affect (Schmidt et al, 2020). In the current study, the CIB Disability subscale demonstrated good internal consistency at both Wave 1, Cronbach's α = .84, and Wave 2, Cronbach's α = .83.…”
Section: Covid-19 Impactmentioning
confidence: 95%
See 1 more Smart Citation
“…Historically, there have been several constructs that are characterized by interoceptive fear or anxiety, most notably anxiety in anticipation of pain-related experiences (e.g., fear during the experience of pain; Rogers, Gallagher, et al, 2020 ), heart-focused anxiety ( Mayorga, Shepherd, Garey, Viana, & Zvolensky, 2021 ), fear of pain ( Vlaeyen, De Jong, Onghena, Kerckhoffs-Hanssen, & Kole-Snijders, 2002 ), anxiety sensitivity (fear about the negative consequences of anxiety sensations; Taylor et al, 2007 ), suffocation fear (fears about breathing dysregulation; McNally & Eke, 1996 ), and health anxiety (anxiety focused on health status or symptoms; Blakey & Abramowitz, 2017 ). There also is emerging research on theoretically relevant interoceptive anxiety, worry, and fear constructs that are specific to the COVID-19 virus (or future pandemics; Schmidt, Allan, et al, 2021 ). This growing anxiety-related COVID-19 literature has the potential to represent narrower pandemic-specific interoceptive anxiety-related constructs.…”
Section: Interoceptive Anxiety-related Processes and The Pandemicmentioning
confidence: 99%
“…Although the impact of COVID-19 has been and continues to be devastating from a public health perspective, it sits on the backdrop of a large history of viral diseases, including Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome, and Ebola ( Ashour, Elkhatib, Rahman, & Elshabrawy, 2020 ; Feldmann, Jones, Klenk, & Schnittler, 2003 ; NovelSwine-Origin Influenza A (H1N1) Virus Investigation Team et al (2009) , among others. Although the impact of COVID-19 on physical health is substantial ( Centers for Disease Control and Prevention, 2021a ), the pandemic is also characterized by widespread acute and chronic stress across personal, educational, occupational, and interpersonal realms of functioning ( Schmidt, Allan, et al, 2021 ; Xie et al, 2020 ).…”
mentioning
confidence: 99%